2018
DOI: 10.25105/jmpj.v11i1.2537
|View full text |Cite
|
Sign up to set email alerts
|

Peran Mediasi E-Satisfaction Dan E-Trust Terhadap E-Loyalty

Abstract: <p><em>As the number of female customers shopping in online clothing stores increases, understanding how female customers</em><em>’ </em><em>e-loyalty is formed and fostered in this type of online store becomes very important. The purpose of this paper is to focus on female online clothing shoppers and to examine the mediating of e-loyalty in the context of online clothing stores: e-satisfaction and e-trust. The number  of respondents is 196 persons who have online clothing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 0 publications
2
9
0
6
Order By: Relevance
“…This research finds that brand satisfaction influences the brand loyalty of the banking industry (Khan et al, 2016a). The other researches also support the existing studies that consumer satisfaction has led to brand loyalty and online satisfaction positively related to online loyalty (Laukkanen, 2012;Hepola et al, 2017;Asih & Pratomo, 2018).…”
Section: Hypothesis Testingsupporting
confidence: 84%
“…This research finds that brand satisfaction influences the brand loyalty of the banking industry (Khan et al, 2016a). The other researches also support the existing studies that consumer satisfaction has led to brand loyalty and online satisfaction positively related to online loyalty (Laukkanen, 2012;Hepola et al, 2017;Asih & Pratomo, 2018).…”
Section: Hypothesis Testingsupporting
confidence: 84%
“…Bismo, Sarjono, & Ferian (2018) found that service quality has a positive and significant effect on customer satisfaction and has a positive but insignificant effect on customer loyalty. Research conducted by Aramita et al (2018) found that not all aspects of quality affect loyalty, that is only tangible, responsive, reliability, and assurance did, whereas empathy only indirectly affects loyalty through consumer satisfaction. Other findings by Su et al (2019) showed that perceptions of service quality, engagement and satisfaction were be good predictors of passenger loyalty, while the direct relationship between perceptions of safety and loyalty has not been confirmed.…”
Section: Introductionmentioning
confidence: 94%
“…Just focuses on results to get to the real thing with the effort. In research (Asih and Pratomo, 2018), women prefer to purchase various goods simultaneously or at the same time. Women are also said to often buy things for themselves and their families at the same time.…”
mentioning
confidence: 99%
“…Because it said that women influence the family where it is said that 74% of families in Indonesia leave financial matters to women who are considered as financial directors in the family so that purchasing decisions in a family depend on women (Revita, 2016). According to women's point of view, going shopping is considered an activity because they enjoy it (Asih and Pratomo, 2018). Female shoppers perceive shopping as a stress reliever that does this activity in a relaxed and time-consuming manner (Asih and Pratomo, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation